The study on the history of Gold Dinar Silver Dirham and comparison with Fiat Money / Fatin Auni Rosli. - Rosli, Fatin Auni (2019)
After the ASEAN currency depreciation crisis of 1997 and 1998 and the current global economic crises, the question of going back to using gold dinar as currency has become a lively discussion. The call was made in 2001 by Tun Dr. Mahathir Mohamed, former Prime Minister of Malaysia, to the Organization of Islamic Country (OIC). Nevertheless, no one optimal method has yet been applied worldwide. So the question arose which is will Arab currency gold dinar be used back in the current economy as a currency? Therefore, this study aims to explore the potential of gold dinar quality as a currency by studying the history of gold dinar and silver dirham based on Islamic history and also made a comparison with our current monetary which is fiat money. This is a qualitative analysis of the library research method technique. Analyzing the text and assessing the potential to provide infrastructure for the implementation of gold dinar was done to obtain the results. The study shows that the implementation of gold dinar as currency in the economy is still inadequate due to many factors and also lack of information regarding this topic, (insufficient supply of gold), inadequate reforms of knowledge and lack of political will (consensus of other nations to use gold dinar as money). In conducting this research, this study assembled secondary data from other people’s research regarding this topic through a library research as the methodology used.This research indicates history of gold dinar and silver dirham, opinion of economic experts, Quranic verse regarding this topic, function of money and many more.